Introduction to public history : interpreting the past, engaging audiences - Lyon, Cherstin M. (American Association for State and Local History book series, 2017)
"Introduction to Public History is the major textbook for students interested in public history. It is divided into three major sections: "Popular History, Academic History, and Public Historians," "Three Questions at the Core of Public History: What to Collect? How to Display? How to Engage Audiences?, and "Moving Forward.""--Provided by publisher